2009
DOI: 10.1021/cg900063q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Size-Tunable Monodispersed Metallic Nickel Nanocrystals without Hot Injection

Abstract: Size-tunable monodispersed hierarchical metallic Ni nanocrystals (58-190 nm in diameter) have been prepared by the reduction of Ni 2+ with hexadecylamine under atmospheric pressure. The diameter of the particles could be tuned by simply changing the reaction time. The products were characterized with X-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscope (TEM), energy-dispersive X-ray (EDX), and selected area electron diffraction (SAED) techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In the presence of the magnetic field, the non-magnetic particles act as voids and break the magnetic circuits resulting in the reduction of bulk magnetization with the increase void concentration. The total magnetization of the ND-Ni composite based on the sum of volume concentration of individual magnetizations is 3.9 emu/g, which corresponds to a bulk value of nickel weight percentage of ~16%; this result is in consonance with values reported in the literature for assemblies of magnetic/non-magnetic particles 43 . When the ND-Ni nanocomposite is dispersed in distilled water, it still shows good magnetic properties, as demonstrated by placing a magnet near to the glass beaker ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…In the presence of the magnetic field, the non-magnetic particles act as voids and break the magnetic circuits resulting in the reduction of bulk magnetization with the increase void concentration. The total magnetization of the ND-Ni composite based on the sum of volume concentration of individual magnetizations is 3.9 emu/g, which corresponds to a bulk value of nickel weight percentage of ~16%; this result is in consonance with values reported in the literature for assemblies of magnetic/non-magnetic particles 43 . When the ND-Ni nanocomposite is dispersed in distilled water, it still shows good magnetic properties, as demonstrated by placing a magnet near to the glass beaker ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…27 The coercivity (H c ) of the Ni nanochains was 133.2 Oe, showing greatly enhanced coercivity compared to the value of bulk Ni (0.7 Oe). 28 It was also higher than those of micron-sized Ni dendritic crystals (77 Oe 12 ) and°owerlike Ni spheres composed of Ni nanoparticles (90 Oe). 29 It has been demonstrated that the magnetic metal nanostructures with shape anisotropy will possess high coercivity.…”
Section: -5mentioning
confidence: 90%
“…This gives us a hint that we can easily adjust the Ms of the film samples for different applications by changing the molar ratio of two elements. The coercivity of bulk Co and Ni is a few tens of Oe 18 and 0.7 Oe, 19 respectively. Compared with their bulk counterparts, the as-prepared Co and Ni films exhibited relatively large coercivity, especially in the perpendicular direction.…”
mentioning
confidence: 99%